Case Report: MYO5B Homozygous Variant c.2090+3A>T Causes Intron Retention Related to Chronic Cholestasis and Diarrhea - Zheng, Yu; Peng, Yuming; Zhang, Shuju; Zhao, Hongmei; Chen, Weijian; Yang, Yongjia; Hu, Zhengmao; Yin, Qiang; Peng, Yu (Frontiers in Genetics, 2022)
Background: Biallelically mutated MYO5B is associated with microvillus inclusion disease (MVID, MIM: 251850), cholestasis, or both. This study aims at validating the splicing alteration and clinical features of a novel intron variant for diagnosis. Case presentation: A homozygous variant of MYO5B, NM_001080467.2:c.2090+3A>T (NP_001073936.1:p.?) in intron 17, was identified in a patient suffering from chronic cholestasis and diahhrea. Functional validation showed that this variant caused 185bp intron retention in its mRNA and was predicted to present a premature translation termination site for myoVb (p.Arg697fs*47) in the head motor domain. In addition, bowel biopsy revealed decreased microvilli and local lesions of microvillus inclusion in the duodena of the patient. The patient presented with neonatal cholestasis, intractable diarrhea, liver cirrhosis, cholelithiasis, hepatic cyst, corneal opacity, and failure to thrive. Conclusions: Our study demonstrated a novel homozygous variant of MYO5B that affected an intron subsequently altering splicing and leading to combined cholestasis and MVID. Our results further supported the underlying genotype-phenotype correlations and extended clinical practice towards its diagnosis and management.